2021
DOI: 10.1002/ghg.2053
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for chitosan‐based membranes in CO2/N2 separation : Structure‐property relationship

Abstract: Extensive research has been conducted on a variety of processes for abating the increasing CO 2 emissions which have been causing adverse effects on the environment. Among these, gas separation membranes have the potential to overcome a number of limitations of existing technologies by reducing the cost of operations and providing an efficient, compact module which can be employed for separating CO 2 from natural gas and post-combustion flue gas streams. Recently, chitosan and its derivatives have proven their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 164 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Chitosan (CS) is a linear polysaccharide obtained by the deacetylation of chitin, an abundant natural polymer, which is cheap and obtained from renewable sources, i.e., the shell of crustaceans. CS has been proven to be a suitable organic framework to manufacture membranes for CO 2 /N 2 membranes separation [10]. The only drawback occurs when the uncontrolled high hydrophilicity compromises the mechanical resistance.…”
Section: Supporting Information Available Onlinementioning
confidence: 99%
“…Chitosan (CS) is a linear polysaccharide obtained by the deacetylation of chitin, an abundant natural polymer, which is cheap and obtained from renewable sources, i.e., the shell of crustaceans. CS has been proven to be a suitable organic framework to manufacture membranes for CO 2 /N 2 membranes separation [10]. The only drawback occurs when the uncontrolled high hydrophilicity compromises the mechanical resistance.…”
Section: Supporting Information Available Onlinementioning
confidence: 99%
“…Several authors have reported that chitosan (CS) is one of the best CO 2 -philic chelants containing hydrogel biopolymer matrix. [33][34][35][36] Moreover, they possess good film forming capability and more comfortable with auxiliary CO 2 -philic chelants compounds (amines, ethylene oxides (EO), aminoalcohols, etc.). [36][37][38][39][40] Hence in our study, the dual-layer flat-bed hydrogel CS biopolymer coated PVTMS composite membranes were prepared and gas transport behavior of the membranes was studied in detail.…”
Section: Introductionmentioning
confidence: 99%